Evaluation of effluent markers cancer antigen 125, vascular endothelial growth factor, and interleukin‐6: relationship with peritoneal transport - Rodrigues, Anabela (2004)
Peritoneal hyperpermeability has been associated with increased levels of effluent vascular endothelial growth factor (VEGF) and interleukin-6 (IL-6). Mesothelial cells can produce various vasoactive substances besides VEGF. A large mesothelial mass may possibly lead to high dialysate VEGF concentrations and may partly explain some cases of peritoneal hyperpermeability during a patient’s early months on peritoneal dialysis (PD). Early peritoneal fast transport may therefore not necessarily be associated with systemic inflammation. To investigate the relationship of effluent markers and peritoneal transport, we measured the appearance rates of cancer antigen 125 (CA125), VEGF, and IL-6 in 4-hour effluents from 69 peritoneal equilibration tests (PETs) using 3.86% glucose solution. At the same time, we measured serum VEGF and IL-6. Our analyses included an early group (EG), whose members had been on PD for 4.6 ± 3.3 months, and a later group (LG), whose members had been on PD for 30 ± 17 months. In EG, dialysate-to-plasma creatinine at 4 hours (D/PCr240) correlated significantly with effluent CA125/min (r = 0.51, p = 0.006) and VEGF/min (r = 0.57, p = 0.001), but not with serum VEGF or IL-6. The values of CA125/min and VEGF/min also correlated (r = 0.40, p = 0.034). Fast transporters in EG had higher effluent CA125 (p = 0.057) and VEGF (p = 0.0001), but not serum or effluent IL-6. In LG, D/PCr240 again correlated significantly with dialysate VEGF(r = 0.51, p = 0.009), but not with CA125. Fast transporters in LG tended to have higher levels of serum and effluent IL-6 and effluent VEGF. We conclude that fast solute transport rates at the beginning of PD are associated with signs of a large mesothelial cell mass and not consistently associated with higher systemic IL-6. The VEGF produced by mesothelial cells can mediate early peritoneal hyperpermeability in some populations. Later, mesothelial mass is lost and is no longer related to increased intraperitoneal VEGF or IL-6.